Polymerization shrinkage stresses in different restorative techniques for non-carious cervical lesions - Correia, Ayla Macyelle de Oliveira [UNESP]; Tribst, João Paulo Mendes [UNESP]; Matos, Felipe de Souza [UNESP]; Platt, Jeffrey A.; Caneppele, Taciana Marco Ferraz [UNESP]; Borges, Alexandre Luiz Souto [UNESP] (Elsevier, 2018)
Objective: This study evaluated the effect of different restorative techniques for non-carious cervical lesions (NCCL) on polymerization shrinkage stress of resins using three-dimensional (3D) finite element analysis (FEA). Methods: 3D-models of a maxillary premolar with a NCCL restored with different filling techniques (bulk filling and incremental) were generated to be compared by nonlinear FEA. The bulk filling technique was used for groups B (NCCL restored with Filtek™ Bulk Fill) and C (Filtek™ Z350 XT). The incremental technique was subdivided according to mode of application: P (2 parallel increments of the Filtek™ Z350 XT), OI (2 oblique increments of the Filtek™ Z350 XT, with incisal first), OIV (2 oblique increments of the Filtek™ Z350 XT, with incisal first and increments with the same volume), OG (2 oblique increments of the Filtek™ Z350 XT, with gingival first) and OGV (2 oblique increments of the Filtek™ Z350 XT, with gingival first and increments with the same volume), resulting in 7 models. All materials were considered isotropic, elastic and linear. The results were expressed in maximum principal stress (MPS). Results: The tension stress distribution was influenced by the restorative technique. The lowest stress concentration occurred in group B followed by OG, OGV, OI, OIV, P and C; the incisal interface was more affected than the gingival. Conclusion: The restoration of NCCLs with bulk fill composite resulted in lower shrinkage stress in the gingival and incisal areas, followed by incremental techniques with the initial increment placed on the gingival wall. Clinical significance: The non-carious cervical lesions (NCCLs) restored with bulk fill composite have a more favorable biomechanical behavior.
Keywords: Composite resins; Dental stress analysis; Finite element analysis; Incremental technique; Non carious cervical lesions; Polymerization